The Experience of Implementing the Board of Trustees' Policy in Teaching Hospitals in Iran: An Example of Health System Decentralization - Leila Doshmangir; Arash Rashidian; Hamid Ravaghi; Amirhosein Takian; Mehdi Jafari (Kerman University of Medical Sciences, 2015)
Background In 2004, the health system in Iran initiated an organizational reform aiming to increase the autonomy of teaching hospitals and make them more decentralized. The policy led to the formation of a board of trustees in each hospital and significant modifications in hospitals' financing. Since the reform aimed to improve its predecessor policy (implementation of hospital autonomy began in 1995), it expected to increase user satisfaction, as well as enhance effectiveness and efficiency of healthcare services in targeted hospitals. However, such expectations were never realized. In this research, we explored the perceptions and views of expert stakeholders as to why the board of trustees' policy did not achieve its perceived objectives. Methods We conducted 47 semi-structured face-to-face interviews and two focus group discussions (involving 8 and 10 participants, respectively) with experts at high, middle, and low levels of Iran's health system, using purposive and snowball sampling. We also collected a comprehensive set of relevant documents. Interviews were transcribed verbatim and analyzed thematically, following a mixed inductive-deductive approach. Results Three main themes emerged from the analysis. The implementation approach (including the processes, views about the policy and the links between the policy components), using research evidence about the policy (local and global), and policy context (health system structure, health insurers capacity, hospitals' organization and capacity and actors' interrelationships) affected the policy outcomes. Overall, the implementation of hospital decentralization policies in Iran did not seem to achieve their intended targets as a result of assumed failure to take full consideration of the above factors in policy implementation into account. Conclusion The implementation of the board of trustees' policy did not achieve its desired goals in teaching hospitals in Iran. Similar decentralization policies in the past and their outcomes were overlooked, while the context was not prepared appropriately and key stakeholders, particularly the government, did not support the decentralization of Iran's health system.